Experimental and numerical analysis of curling behavior of natural hydraulic lime - cement based mortars. (March 2019) - Jaafri, Reda; Samouh, Hamza; Roziere, Emmanuel; Alam, Syed Yasir; Wisniewski, Vincent; Loukili, Ahmed
Abstract: This paper aims to identify the parameters influencing the curling phenomenon, and to understand the influence of cement substitution by increasing proportions of Natural Hydraulic Lime (NHL) on the kinetics and the final curling magnitude. The developed experimental approach shows that the curling is mainly driven by the progress of the drying front in the specimen depth. A common curve curling-drying depth is observed for all the studied mortars independently of their mix-design. Results also show that NHL leads to a significant reduction in the curling's final amplitude and delayed its start time due to its influence on the microstructure of studied mortars. Based on the experimental results and, mainly, on the spatio-temporal internal relative humidity evolutions, a poroviscoelastic model which incorporates well-accepted mechanisms for shrinkage is proposed. The model is able to reproduce the evolution of curling and to estimate the viscoelastic response of the studied mortars. The curling starts developing as soon as the material develops sufficient rigidity, and its magnitude is mainly related to the viscoelastic-aging modulus which is about the same for all the studied mortars.